Poland syndrome with some rare associations, and brief literature review (Indian Journal of Case Reports, 2017)
Poland syndrome (PS) is a rare congenital condition with predominant unilateral chest wall deformity due to hypoplasia of the pectoralis muscles. However, its clinical features are highly variable as all the features may not be present in one individual or it may present with some rare associations or complications as being reported here. A 6-year-old boy was diagnosed, for the first time, as a case of PS but, detailed examination and work up revealed two rare associations and/or incidental findings of this disorder, namely, Dandy-Walker variant and partial anomalous pulmonary venous return. Hence, a detailed clinical examination and a through workup are mandatory to quantify the disease spectrum of this rare disorder.